A PROPOSAL OF DIGITAL IDENTITY MANAGEMENT USING BLOCKCHAIN (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2024)
Digital identity is the representation of a person in the digital environment. Nowadays, digital identity has become a very important topic when most activities are moved to the online world. To be secured and respect data privacy, this digital identity must be controlled by its owner, not any other third parties. This paper aims to propose a system for digital identity, presenting its architecture, features, and implementation specifications. This system brings advantages that will also be exposed along with real-life use case scenarios, all proving the necessity of transitioning to a modern identity management model like the Self-Sovereign Identity model. The Self-sovereign identity model is based on blockchain and is fundamental for the digital identity system conceived through research.
Keywords: Self-Sovereign Identity; Self-sovereign identity; Digital identity management; Digital Identity Management; Blockchain; Verifiable Credentials; Verifiable credentials